Penguatan Daya Saing UMKM Menggunakan Analisis SWOT (Studi Kasus: Kampung Keramik Dinoyo Kota Malang) - Sabilla, Rizki; Ulyah, Nadiratul; Misriyatun, Misriyatun; Rizkiani, Iftitah; Bastomi, Mohamad (CV. Era Digital Nusantara, 2024)
This study explores the strategic marketing analysis of ceramic-based Micro, Small, and Medium Enterprises (MSMEs) in Kampung Keramik Dinoyo, Malang City. It investigates the challenges faced by these MSMEs in product innovation and marketing strategies, emphasizing the implementation of a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The research highlights the unique strengths such as diverse ceramic designs, local artisans' expertise, rich cultural heritage, and strategic location in Malang City. However, weaknesses such as limited innovation in product design and inadequate promotion have been identified. Opportunities include the potential for local tourism enhancement, growth in the local creative industry, international market potential, and advancements in digital technology. Threats encompass the emergence of new competitors, market demand fluctuations, governmental regulations affecting the working environment, and declining purchasing power. Based on the SWOT analysis results, strategies are proposed to leverage strengths and opportunities while mitigating weaknesses and threats. These strategies include fostering innovation through workshops, enhancing digital marketing efforts, collaborating with local designers, and gaining support from local governments. The findings aim to contribute to the sustainability and competitiveness of ceramic MSMEs in Kampung Keramik Dinoyo, ensuring their economic contributions and cultural heritage preservation.